Changes in farmer animal health and biosecurity knowledge, attitudes and practices: Insights from Cambodia and Laos. Issue 4 (4th October 2021) - MacPhillamy, Isabel; Olmo, Luisa; Young, James; Nampanya, Sonevilay; Suon, Sothoeun; Khounsy, Syseng; Windsor, Peter; Toribio, Jenny‐Ann; Bush, Russell
Abstract: Livestock agriculture in Cambodia and Laos is severely affected by endemic and exotic transboundary animal diseases, impacting household livelihoods and food and nutritional security. Collaborative animal health and biosecurity projects were conducted in each country between 2015 and 2019 aimed at increasing smallholder livestock production through mainly knowledge‐based interventions in large ruminant disease prevention, nutrition, reproduction and marketing access. This study's objectives were to identify baseline animal health and biosecurity knowledge, attitudes and practices (KAP) of farmers, and temporal changes in key attitudes and practices associated with improved knowledge. Data for each country were analysed separately, and a formal between‐country comparison was avoided due to major implementation and management differences. Binomial logistic regression without random terms compared the overall knowledge scores between 2015 and 2018 in each country, and binomial logistic regression with random terms was used to investigate possible associations between animal health and biosecurity knowledge scores and attitudes and practices. In Cambodia, the average animal health and biosecurity knowledge score increased from 4.8 (±2.2)/17 in 2015 to 13.0 (±2.8)/17 in 2018 ( p < .0001). In Laos, the average scores improved from 7.2 (±2.5)/12 in 2015 to 7.9 (±2.9)/12 in 2018 ( p = .0003). Clinical signs of foot‐and‐mouth disease were accurately reported by 100% of Cambodian and 88% of Lao project farmers, and overall, attitudes and practices improved in both countries over the study period. The belief that vaccination can improve livestock value was associated with increasing knowledge in both countries (Cambodia: OR 1.45, 95% CI 1.24–1.68, p < .0001; Laos: OR 1.43, 95% CI 1.16–1.75, p = .0006) as was the use of the services of village para‐veterinarians if they had better training (Cambodia: OR 1.76, 95% CI 1.20–2.58, p = .004; Laos: OR 2.02, 95% CI 1.19–3.41, p = .009). However, the source of livestock information (District veterinary officials) was the only practice associated with knowledge in both Cambodia and Laos. The influence of resource scarcity on farmer decision making and knowledge measures was considered of particular relevance to the findings.